Guns germs and steel a short history of everybody for the last 13000 years - Jared Diamond (London Vintage, 2017)
A book of big questions, and big answers' Yuval Noah Harari, bestselling author of SapiensWhy has human history unfolded so differently across the globe? And what can it teach us about our current crisis?red Diamond puts the case that geography and \ogeography, not race, moulded the contrasting fates of Europeans, Asians, Native Americans, sub-Saharan Africans, and boriginal Australians.An ambitious synthesis of history, biology, ecology and linguistics, Guns, Germs and Steel is a ground-breaking and humane work of popular science that can provide expert insight into our modern world.
Keywords: Culture